The Rhetoric of Topics and Forms - Zocco, Gianna (XXI. Congress of the ICLA - Proceedings, 2021)
Although the question of prioritizing either the level of content or that of form has often been controversial, most contributions of this volume treat them as internally connected. They undertake analyses of motifs, metaphors, and topoi, and thereby not only prove the relevance of rhetorical and thematic study, but also contribute to flourishing fields such as literary multilingualism, literature and emotions, and ecocriticism.